Popular Terroir: Bande Dessinée as Pastoral Ecocriticism? - Margaret C Flinn (Studies in 20th & 21st Century Literature, 2018)
This article analyses a corpus of French comic books (including series and one-shots) published since 2010 that share a thematic focus on agriculture. I argue that this mini-explosion in French comics publishing that crosses various generic and reading public boundaries can be viewed as a contemporary iteration of the pastoral. This ever-expanding body of texts is guided by ecocritical preoccupations, through their engagement with terroir. Because of the cultural connotations of terroir in modern and contemporary France, these comics are situated at the intersection of environmentally progressive and culturally conservative discourses.
Keywords: Pastoral; terroir; bande dessinée; France; environmentalism; ecocriticism; agriculture; viticulture